2011
DOI: 10.2304/ciec.2011.12.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating ‘Belonging’ in Belonging, Being and Becoming: The Early Years Learning Framework for Australia

Abstract: In this article, the authors interrogate the use of 'belonging' in Belonging, Being and Becoming: the Early Years Learning Framework for Australia (EYLF), Australia's first national curriculum for early childhood education and care settings and, from the authors' interrogation, possibilities are offered for thinking about and working with the EYLF in critical and transformative ways. In order to scaffold their interrogation, the authors develop a cartography of understandings of belonging drawn from diverse di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(145 citation statements)
references
References 21 publications
3
136
0
6
Order By: Relevance
“…One example of universal supports is the Early Years Learning Framework (EYLF), a national framework for early childhood curriculum. The framework pertains to early childhood services delivered to children from birth to school entry and includes range of learning outcome areas (including communication) and guidelines for attainment in these areas (Sumsion et al, 2009) Associations between SaLD and HRQoL found in this research support the use of HRQoL measures in speech-language pathology, prioritisation and outcome measurement.…”
Section: Need For Early Interventionmentioning
confidence: 67%
“…One example of universal supports is the Early Years Learning Framework (EYLF), a national framework for early childhood curriculum. The framework pertains to early childhood services delivered to children from birth to school entry and includes range of learning outcome areas (including communication) and guidelines for attainment in these areas (Sumsion et al, 2009) Associations between SaLD and HRQoL found in this research support the use of HRQoL measures in speech-language pathology, prioritisation and outcome measurement.…”
Section: Need For Early Interventionmentioning
confidence: 67%
“…Within the National Reform Agenda, reforms to early childhood education and care were 'fast-tracked', in part because of their perceived redemptive appeal (Sumsion et al, 2009). Shortly after taking office, Rudd (2008) made the long-awaited, historic and highly symbolic 'Apology to Australia's Indigenous Peoples'.…”
Section: The Australian Political and Policy Contextmentioning
confidence: 99%
“…The Framework, in turn, was to become an integral component of a new National Quality Standard that early childhood services would be required to meet to be eligible for government funding. As co-leader (Author 1) and member (Author 2) of the consortium of academics, consultants, peak bodies, employer organisations and practitioners (the Consortium) awarded the tender to work with the Council of Australian Governments to write the Framework, we were embroiled in intense negotiations throughout the scant nine months (September 2008 to May 2009) of its development (Sumsion et al, 2009).…”
Section: The Australian Political and Policy Contextmentioning
confidence: 99%
See 2 more Smart Citations